An automated tracking system for Caenorhabditis elegans locomotor behavior and circadian studies application - Simonetta, Sergio Hernan (2007)
ADP-ribosylation of host cell proteins is a common mode of cell intoxication by pathogenic bacterial toxins. Antibodies induced by immunization with inactivated ADP-ribosylating toxins provide efficient protection in case of some secreted toxins, e.g., diphtheria and pertussis toxins. However, other ADP-ribosylating toxins, such as Salmonella SpvB toxin, are secreted directly from the Salmonella-containing vacuole into the cytosol of target cells via the SPI-2 encoded bacterial type III secretion system, and thus are inaccessible to conventional antibodies. Small-molecule ADP-ribosylation inhibitors are fraught with potential side effects caused by inhibition of endogenous ADP-ribosyltransferases. Here, we report the development of a single-domain antibody from an immunized llama that blocks the capacity of SpvB to ADP-ribosylate actin at a molar ratio of 1:1. The single-domain antibody, when expressed as an intrabody, effectively protected cells from the cytotoxic activity of a translocation-competent chimeric C2IN-C/SpvB toxin. Transfected cells were also protected against cytoskeletal alterations induced by wild-type SpvB-expressing strains of Salmonella. This proof of principle paves the way for developing new antidotes against intracellular toxins